Spillover and genome selection of the gut parasite Nosema ceranae between honey bee species - Wei, Xiuxiu; Evans, Jay D.; Chen, Yanping; Huang, Qiang (Frontiers in Cellular and Infection Microbiology, 2022)
Nosema ceranae is a honey bee gut parasite that has recently spilled to another honey bee host through trading. The impact of infection on the native host is minor, which is substantial in the novel host. In this study, artificial inoculation simulated the parasite transmission from the native to the novel host. We found that the parasite initiated proliferation earlier in the novel host than in the native host. Additionally, parasite gene expression was significantly higher when infecting the novel host compared with the native host, leading to a significantly higher number of spores. Allele frequencies were similar for spores of parasites infecting both native and novel hosts. This suggests that the high number of spores found in the novel host was not caused by a subset of more fit spores from native hosts. Native hosts also showed a higher number of up-regulated genes in response to infection when compared with novel hosts. Our data further show that native hosts suppressed parasite gene expression and arguably sacrificed cells to limit the parasite. The results provide novel insights into host defenses and gene selection during a parasite spillover event.